Excepcionalidade, deficiência ou necessidades educacionais especiais: o aluno como constituinte do campo da educação especial - Souza, Sirleine Brandão de (2018)
In as much as special education constitutes a particular field of knolwedge, whose locus is situated in a determined social space, that has as its premise to offer schooling for students with specific characteristics that interefere in this process, this study sought to verify and analyze the changes, permanences, and disruptions to its identity as manifest in the specialised literature by means of a distinct characteriation of the populations it is destined to serve and the close relationship between the the academic-scientific field and the educational policies, marked by the transformations resulting from determined historical moments. The studies of Pierre Bourdieu (1983, 1991, 2004, 2005, 2008, 2015) made up the theoretical foundation of the investigation, specifically the concepts of field and language. To this end, data was collected from texts published in the periodical Revista Brasileira de Educação Especial, considered the most respected in the area, from its first edition in 1992 until the year 2015. The methodological proceedures of the research encompass, in the first phase, the choice of sections to be analized, resulting in the selection of essays, research reports and articles. The second phase was a survey of texts that establish a wider discussion of special education, resulting in a total of 102 texts following this tendency. The third phase consisted of an analysis of the discourse produced, through a deep reading of 30 texts selected from survey carreid out in the second phase. It could be concluded that in the field of special education the intimate relationship, both evident and inevitable, between the political field and the academic field reflects, on one hand, the disputes about the characterization of these students who constitute this field, and on the other hand, the temporal coexistence of different perspectives, which are at the same time distinct and antagonistic, that configure a multifaceted and diverse identity, reflecting the very contradictory movement of society and, consequently, social policies